The Gurkha and the Lord of Tuesday - Hossain, Saad Z. (Tor, 2019)
When the djinn king Melek Ahmar wakes up after millennia of imprisoned slumber, he finds a world vastly different from what he remembers. Arrogant and bombastic, he comes down the mountain expecting an easy conquest: the wealthy, spectacular city state of Kathmandu, ruled by the all-knowing, all-seeing tyrant AI Karma. To his surprise, he finds that Kathmandu is a cut-price paradise, where citizens want for nothing and even the dregs of society are distinctly unwilling to revolt. Everyone seems happy, except for the old Gurkha soldier Bhan Gurung. Knife saint, recidivist, and mass murderer, he is an exile from Kathmandu, pursuing a forty-year-old vendetta that leads to the very heart of Karma. Pushed and prodded by Gurung, Melek Ahmer finds himself in ever deeper conflicts, until they finally face off against Karma and her forces. In the upheaval that follows, old crimes will come to light and the city itself will be forced to change.